Visual Field Examination in Glaucoma Patients : Humphrey Visual Field Analysis vs Amsler Grid - Ivana Tanoko; Fifin L Rahmi (Majalah Oftalmologi Indonesia, 2017)
Introduction and Objective: Glaucoma is the leading cause of global irreversible blindness, signed by glaucomatous optic neuropathy related to visual field defect. The purpose of the study is comparing visual field defect examination using HVFA to Amsler Grid in glaucoma patient at dr. Kariadi Hospital. Methods: This is a cross-sectional study. Amsler Grid were performed to the patients who have reliable HVFA at last 6 months and presented as descriptive analytic results. Result: There were 40 eyes involved in this study from 27 patients (15 men, 12 women), 26-68 years old and visual acuity 1/60-6/6. Seventeen eyes showed visual field defect in HVFA and Amsler Grid had average MD - 24.97 dB, CDR 0.89 and RNFL thickness 51.74. We found that 11 eyes didn’t showed in both of examination had average MD -8.06, CDR 0.63 and RNFL thickness 103.23 and those parameters are significantly different to the 17 eyes before (p<0.05). Data from 12 eyes that showed visual field defect only one of examination (9 only in HVFA and 3 in Amsler Grid) didn’t show difference statistically each other. Conclusion: HFVA and Amsler Grid seemed to be comparable in detecting visual field defect in advanced glaucoma.